2016
DOI: 10.18632/oncotarget.14268
|View full text |Cite
|
Sign up to set email alerts
|

The GSK461364 PLK1 inhibitor exhibits strong antitumoral activity in preclinical neuroblastoma models

Abstract: Polo-like kinase 1 (PLK1) is a serine/threonine kinase that promotes G2/M-phase transition, is expressed in elevated levels in high-risk neuroblastomas and correlates with unfavorable patient outcome. Recently, we and others have presented PLK1 as a potential drug target for neuroblastoma, and reported that the BI2536 PLK1 inhibitor showed antitumoral actvity in preclinical neuroblastoma models. Here we analyzed the effects of GSK461364, a competitive inhibitor for ATP binding to PLK1, on typical tumorigenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 64 publications
1
23
0
1
Order By: Relevance
“…Another major field in PLK1 research is developing PLK1 small‐molecule inhibitors as drug therapies in diseases such as cancer (reviewed in Elizabeth, Gutteridge, Ndiaye, Liu, & Ahmad, ; Murugan et al, ). Numerous studies have tested PLK1 inhibitors, including BI2536, as potential cancer therapeutics for advanced metastatic tumors, including prostate cancer (Hou et al, ; Zhang et al, ), lung cancer (Awad et al, ; Breitenbuecher et al, ), neuroblastoma (Pajtler et al, ), and non‐Hodgkin's lymphoma (Vose et al, ) to name a few. These studies suggest elevated levels of PLK1 expression in highly metastatic and advanced cancers, leads to chromosome instability and aneuploidy (Yamamoto et al, ), providing these cells an advantage to overgrow and invade tissues.…”
Section: Plk1‐scaffold Interactionsmentioning
confidence: 99%
“…Another major field in PLK1 research is developing PLK1 small‐molecule inhibitors as drug therapies in diseases such as cancer (reviewed in Elizabeth, Gutteridge, Ndiaye, Liu, & Ahmad, ; Murugan et al, ). Numerous studies have tested PLK1 inhibitors, including BI2536, as potential cancer therapeutics for advanced metastatic tumors, including prostate cancer (Hou et al, ; Zhang et al, ), lung cancer (Awad et al, ; Breitenbuecher et al, ), neuroblastoma (Pajtler et al, ), and non‐Hodgkin's lymphoma (Vose et al, ) to name a few. These studies suggest elevated levels of PLK1 expression in highly metastatic and advanced cancers, leads to chromosome instability and aneuploidy (Yamamoto et al, ), providing these cells an advantage to overgrow and invade tissues.…”
Section: Plk1‐scaffold Interactionsmentioning
confidence: 99%
“…Small molecule kinase inhibitor screening by Grinshtein et al [177] identified Polo-like kinase 1 (PLK-1) as the potential target for NB tumor initiating cells. To that end, a study by Pajtler et al [178] demonstrated that imidazotriazine (GSK461364), a competitive inhibitor for ATP binding to PLK1 which is in clinical development promoted cell death, inhibited clonal expansion and exerted anti-tumoral activity in vivo.…”
Section: Csc-targeted Therapymentioning
confidence: 99%
“…Pajtler et al [178] Berberine Vimentin, fibronectin, E-cadherin, laminin, Smad, PI3/Akt, Ras-Raf-ERK Naveen et al [179] XAV939 a small molecule tankyrase (TNKS) inhibitor…”
Section: Drug Targetsmentioning
confidence: 99%
“…PLK1'in inhibisyonu, hücre döngüsünün dur-durulmasına neden olmakta ve apoptozu indüklemektedir. 71,72 Pek çok kanserden farklı olarak, TP53 mutasyonları nöroblastomda daha az görülmektedir. TP53 aracılı hücre ölüm yolağı-nın negatif bir düzenleyicisi olan PPM1D'nin inhibisyonu, CHK2/ TP53 aracılığıyla apoptozu indüklemek için yeni bir yaklaşım olarak öneril-miştir.…”
Section: Hedefe Yöneli̇k Tedavi̇ Yaklaşimi Ve Gelecek Perspekti̇flerunclassified